Quality Practice Teaching Experience in Cooperating Schools: Building Foundations for Effective Teacher Education - Santiago, Lilia M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
A study was conducted in the Tarlac City Schools Division, Philippines, to evaluate the practice teaching experiences of student interns in line with Republic Act No. 7722, known as the "Higher Education Act of 1994," which underscores the significance of quality pre-service teacher education in enhancing educational standards. The research aimed to assess the preparedness of student teachers by examining various factors including orientation activities, relationships with the school community, accessibility of practicum sites, and the quality of support services. The methodology involved descriptive analysis of orientation sessions conducted by supervisors and cooperating educators, which included familiarization with school facilities, rules, classroom routines, and instructional material development. Additionally, the study evaluated student interns' involvement in lesson planning and teaching demonstrations while identifying challenges through questionnaires, interviews, and portfolio reviews. Findings revealed that student interns rated their overall practice teaching experience as "Very Good" across multiple dimensions such as orientation activities and community engagement. The interns effectively utilized instructional materials and were acknowledged for their exceptional performance during their internships. This study provides valuable insights into the effectiveness of practice teaching programs and contributes to the preparation of future educators in the Philippines, supporting the national objective of improving educational quality to meet global standards.